O papel da avaliação na constituição das identidades profissionais docentes - Bressane, Ana Carolina Rebouças (2014)
The present study aims to identify possible relationships among evaluative processes developed at the school and the establishment of professional teaching identities. Specifically aims to identify evaluative practices that produce a greater degree of legitimacy and recognition by the subject teacher, which, in turn, may contribute to the processes of identity negotiation. The work of data analysis is oriented in a qualitative perspective. The data collection was done in two private institutions in the city of São Paulo. The selected institutions have formalized their practices work of institutional assessment, which has three pillars: the evaluation of the structure and school functioning, the evaluation of the performance of the educators (teachers, managers and employees) and the assessment of the student s learning. Six subjects were interviewed, with, two coordinators and four professors of Basic Education. Individual interviews with teachers and for the coordinators for later transcription were performed. The interview scripts are characterized as semi - structured and were formulated for the teachers, who put themselves in a position of reviews and coordinators, which are those that, usually, generally assume the role of appraisers. The data collection was as follows: the coordinator stated, in his opinion, two teachers from the same institution for the interview, one that was most closely identified with the school s proposal and other that was less identified with the proposed school. Six categories were used for the data collection. They are: choice of subjects, evaluation practices developed at the institution X practices that contributed to the teacher s professional growth; evaluation s criterion, criteria for the allocation of judgments; refusals and trading strategies ; legitimacy degree. The data results pointed to some aspects: the formative assessment was indicated by the teachers as the a contributor to the professional growth , the surveyed schools do not reverted the data obtained in the evaluations of teachers in their training processes , the lack of participation of the teachers in defining the evaluation criteria interfered with clarity as to what is expected by the institution as " teacher quality ", the relationship that teachers have established with the reviewer favored the acceptance of delivered judgments in situations of evaluation, a partnership established that the evaluated subject reported to the evaluator ensured greater legitimacy to the evaluation processes . This work highlights the importance of the evaluative processes of an educational nature in the constitution of professional teaching identities and the relevance of the reported link between subject and evaluator subject to processes of identity negotiation